Flammability as an ecological and evolutionary driver - Pausas, Juli G.; Keeley, Jon E.; Schwilk, Dylan W. (The Journal of ecology, 2017)
1. We live on a flammable planet yet there is little consensus on the origin and evolution of flammability in our flora. 2. We argue that part of the problem lies in the concept of flammability, which should not be viewed as a single quantitative trait or metric. Rather, we propose that flammability has three major dimensions that are not necessarily correlated: ignitability, heat release and fire spread rate. These major axes of variation are controlled by different plant traits and have differing ecological impacts during fire. 3. At the individual plant scale, these traits define three flammability strategies observed in fire-prone ecosystems: the non-flammable, the fast-flammable and the hot-flammable strategy (with low ignitability, high flame spread rate and high heat release, respectively). These strategies increase the survival or reproduction under recurrent fires, and thus, plants in fire-prone ecosystems benefit from acquiring one of them; they represent different (alternative) ways to live under recurrent fires. 4. Synthesis. This novel framework based on different flammability strategies helps us to understand variability in flammability across scales, and provides a basis for further research.